AN OVERVIEW OF AYURVEDIC MANAGEMENT OF STHAULYA W.S.R OBESITY - Aggarwal, Monica (International Journal of Ayurveda and Pharma Research, 2019)
Due to rapid modernization in recent years, presence of nutritional abundance and sedentary lifestyle, metabolic disorders have emerged rapidly. Obesity is one of the nutritional lifestyle disorder affecting both developed and developing countries. Obesity is a disorder characterized by increased body weight and excess fat deposition. Obesity is the root cause of overconsumption of calories and reduced physical activity which lead to serious health complications. Multifactorial in nature in which environmental, lifestyle and genetic factors play an equally important role in its etiology. Ayurveda is one of the most ancient sciences of world describing basic and applied principles of health, disease and its management. In Ayurveda, obesity has been described under the caption Sthaulya. Sthaulya is mentioned under Santarpanjanyavikara (over nourishment of body). Sthaulya is among one of the 8 unwanted diseases mentioned by Acharyas. Using fatty diet, decreased physical activity and hereditary factors contribute to its etiology ultimately causing derangement of Agni of Medadhatu. This produces excess of Meda or fat. Sufficient focus has been given in the management of Sthaulya in form of diet and drugs to control the disease in Samhita. Ayurvedic treatment is addressed by correction of dietary patterns in form of Nidana Parivarjana and Pathya Aahar –Vihara and Aptarpana Chikitsa to correct vitiated Dosha and Agni. Obesity is a preventable lifestyle disorder which can be easily addressed by keeping an initial check on one’s dietary pattern. Medicine usage play a secondary role, keeping at par various metabolic disorders like diabetes, hypertension etc. It fulfills the first and foremost motto of Ayurveda which is prevention of disease being less expensive and more approachable than treatment.